Predation by Engytatus varians (Distant) (Hemiptera: Miridae) on Bactericera cockerelli (Sulcer) (Hemiptera: Triozidae) and two Spodoptera species. Issue 2 (9th April 2020) - Pineda, S.; Hernández-Quintero, O.; Velázquez-Rodríguez, Y. B.; Viñuela, E.; Figueroa, J. I.; Morales, S. I.; Martínez-Castillo, A. M.
Abstract: Predation by Engytatus varians (Distant) adults on different development stages of the prey species Bactericera cockerelli (Sulcer) (egg, second, and third nymphal instars), Spodoptera exigua (Hübner) and Spodoptera frugiperda (J. E. Smith) (egg, first, and second larval instars) was evaluated using tomato ( Solanum lycopersicum L.) leaflets or plants. These insects are the primary pest of several agriculturally important crops. The influence of E. varians age on the predation capacity was also analysed. Engytatus varians females consumed significantly more B. cockerelli eggs and nymphs than males. Additionally, female predators consumed significantly more second than third instar prey at two predator ages, while males consumed significantly more the second instar than third instar prey at all predator ages. In most of the cases, females also consumed significantly more S. exigua and S. frugiperda eggs than males; however, in terms of larvae consumption, this difference was observed only in some predator ages. Females consumed more the first than second instar S. exigua than males, whereas this behaviour was only observed in males when the predators were 15 and 17 days old. No significant differences were observed in the consumption of first and second instar of S. frugiperda for both sexes of the predators. Predator age did not cause any systematic effects on the predation rates of any prey species. Based on these results, we confirmed that E. varians has potential as a biological control agent for B. cockerelli and also for the Spodoptera species bioassayed.